PROSES BERPIKIR SISWA TUNADAKSA CEREBRAL PALSY DALAM MENDEFINISIKAN BANGUN RUANG GEOMETRI - Idhami, Tantri Cahya; Susanto, S; Yudianto, Erfan; Setiawan, Toto Bara; Monalisa, Lioni Anka (Department of Mathematics Education , University of Jember, 2018)
Abstract.The process of thinking is mental activity that experiences disequlibrium, assimilation, accommodation or equilibrium to define, determine decisions and draw conclusions on a geometric problem. The purpose of the study was to determine the thinking process of quadruple cerebral palsy students to define geometric space. This research is a type of descriptive research through a qualitative approach. Data collection methods used are worksheets and interviews. The subject of the study was carried out to 2 students with cerebral palsy who were sitting in class VIII of the Extraordinary Daksa Middle School of the Disabled Children (SMPLB-D YPAC) Kaliwates-Jember. The results showed that both subjects experienced disequilibrium on topic I students' initial knowledge of geometrical space (prisms, beams and cubes), and assimilation on topic II related to similar examples of geometrical space (prisms, beams and cubes), before finally accommodation when paused before answering correctly the questions from the researcher and before retelling the answers that have been written when answering the questions on topic III which is the core of this research, that is knowing the thinking process of students tundaksa cerebral palsy in defining geometric space constructs (beam prisms and cubes). Keywords: The Process of Thinking, Cerebral Palsy Students, Geometry